2020
DOI: 10.1108/imr-12-2018-0360
|View full text |Cite
|
Sign up to set email alerts
|

International social entrepreneurship and social value creation in cause-related marketing through personal relationships and accountability

Abstract: PurposeDrawing on the resource-based view (RBV) and literature on relational embeddedness and network ties, we examine how personal relationships of international social entrepreneurs and accountability of social enterprises influence social value creation in cause-related marketing (CRM) of three UK-based international charities. The study also explores how personal relationships of international social entrepreneurs affect accountability of social entrepreneurship for social value creation of non-profit orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 124 publications
0
15
0
2
Order By: Relevance
“…This means that all incoming monetary flows are naturally destined to their institutional activities and mission (Civitillo, 2020). NPOs can undoubtedly generate benefits in terms of social value production (Porter and Kramer, 1999;Wondolleck and Yaffee, 2000;Smith, 2008), also at international level (Bruce, 1995;Eng et al, 2020). In the future, such mission is expected to be even more pursued by the efficient governance, management and marketing of their IC and SC.…”
Section: Discussionmentioning
confidence: 99%
“…This means that all incoming monetary flows are naturally destined to their institutional activities and mission (Civitillo, 2020). NPOs can undoubtedly generate benefits in terms of social value production (Porter and Kramer, 1999;Wondolleck and Yaffee, 2000;Smith, 2008), also at international level (Bruce, 1995;Eng et al, 2020). In the future, such mission is expected to be even more pursued by the efficient governance, management and marketing of their IC and SC.…”
Section: Discussionmentioning
confidence: 99%
“…he found that the structure and planning of social enterprises are important in addition to the education social entrepreneurs receive. Eng (2020) discussed the relationship between international social entrepreneurship and personal relationships. According to his results.…”
Section: Social Entrepreneurshipmentioning
confidence: 99%
“…Oleh karena itu perlu diperhatikan kembali hubungan personal antar karyawan whiz prime hotel dan tamu agar tamu merasa nyaman menginap di whiz prime hotel. Hubungan personal yang dibangun dapat menciptakan keterikatan antara konsumen dengan perusahaan [17].…”
Section: Manfaat Personalunclassified